Pengaruh Penerapan Healthcare Infection Control Practices Advisory Committee Terhadap Kejadian Infeksi Saluran Kemih Terkait Penggunaan Kateter - Sitepu, Wendy Isman (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2019)
An estimated 0,2-4,8 Catheter-associated Urinary Tract Infection (CAUTI) cases 1.000 catheter-days affected around the world. CAUTI not only has affected the patient but also has became a burden on hospital. Many prevented CAUTI guidelines has developed, one of them is issued by Healthcare Infection Control Practices Advisory Committe (HICPAC). The study aimed to evaluate HICPAC guideline decreasing CAUTI rate. A quasi-experimental study was performed to ass’s effectiveness HICPAC guidelines with two group pretest-posttest approach patients with catheter 150 samples each. Before implementation, all medic staff was explained and trained about the guideline. All medical staff was assessed their knowledge, attitudes, and behavior before and after implementation. Chi-square and Wilcoxon tests were performed. There were 13 CAUTI cases, with 11 cases before implementation and the other cases after implementation (p-value: 0,02). After implementation, knowledge, attitude, and behavior medical staff increased (p-value < 0,05). From the result, implementation HICPAC guideline decreases CAUTI rate and increase knowledge, attitude, and behavior significantly. Implementation HICPAC guidelines could be used easily by all medical staff integrated with the medical record. Commitment implementation the guideline becomes important to decreased CAUTI rates.